Capabilities and Innovative Performance in the Brazilian Agricultural Machinery Industry - Passuello Ruffoni, Estêvão; Maciel Reichert, Fernanda (Review of Business Management, 2022)
Purpose – This study identifies how Brazilian agricultural machinery manufacturers combine different capabilities to innovate. This industry has potential to increase productivity in agriculture, a sector that is notably relevant in Brazil, one of the main food and agricultural commodities producers in the world. Theoretical framework – Firms were approached through the lens of a four innovation capabilities model (development, operations, management and transactions). Previous researches about innovation in the machinery and equipment industry were deepened to support the results obtained. Design/methodology/approach – To identify the combinations of innovation capabilities, fuzzy-set QCA (Comparative Qualitative Analysis) technique was applied. Data were collected through a survey, conducted with 103 Brazilian companies. Findings – Agricultural machinery manufacturers innovate by two combinations of capabilities: development, operations and management (DC*OC*MC), or operations and transactions (OC*TC). Innovation emerges when excellence in manufacturing is complemented by improvements in existing products and in managerial processes (DC*OC*MC), or in negotiation skills and commercialization processes (OC*TC). Research, Practical & Social implications – Previous researches had already identified the machinery and equipment industry, of emerging economies, as focused on production-related enhancements. However, the present study demonstrates that this is not sufficient to firms innovate. As practical implication, we indicate two routes to agricultural machinery companies achieve a high innovative performance. Originality/value – Researches about innovation in the machinery and equipment industry generally aim to understand only how firms develop new products and manufacturing processes. The study fills a gap when approaching this industry through broader lenses, demonstrating the relevance of new managerial and transactional processes development for these firms. Keywords – Innovation, Innovation Capabilities, Machinery and Equipment Industry, Agricultural Machinery, fsQCA